Membangun Kesadaran Masyarakat Desa Bagik Manis Melalui Pelatihan Penggunaan APAR yang Tepat dan Efektif - Wiryajati, I Ketut; I Wayan, Joniarta; Adnyani, Ida Ayu Sri; Aljibran, Aljibran; Fitrirayani, Gadis Ariva (Universitas Mataram, 2025)
Fire is a major disaster threat that can cause significant damage, especially in rural areas with limited firefighting resources. Bagik Manis Village, located in Sambelia District, East Lombok Regency, is highly vulnerable due to dense settlements, simple electrical installations, and limited community knowledge of fire prevention. This highlights the need for training on the use of Portable Fire Extinguishers (APAR) to improve the community’s capacity for quick and effective emergency response. The training was participatory and included several stages: fire hazard awareness, basic APAR introduction, PASS technique demonstration (Pull, Aim, Squeeze, Sweep), hands-on practice, simple simulations, and evaluations. Knowledge and skills were assessed through tests and observation. Results showed significant improvement in all indicators. Basic knowledge increased from 26% to 87%, understanding of the PASS procedure from 18% to 82%, practical skills from 13% to 77%, and collective awareness from 35% to 92%. The training effectively improved fire knowledge, skills, and preparedness culture. It is recommended to continue the program regularly, form fire preparedness groups, and ensure APAR availability in households and public facilities.